Antibacterial Activity of Ethanolic Extract from Tempuyung Leaf (Sonchus arvensis L.) againts Salmonella typhi by In Vitro Study - Rinda Yanuarisa; Dini Agustina; Ali Santosa (Faculty of Medicine, University of Jember, 2016)
Tifoid fever caused by Salmonella typhi (S. typhi) is endemic disease in Indonesia. S. typhi begin to resist to chloramphenicol, so it is necessary to study about natural material as traditional medicine such as tempuyung. The aim of this research was to study antibacterial activity and Minimum Inhibitory Concentration (MIC) of ethanolic extract from tempuyung leaf (Sonchus arvensis L.) againts growth of S. typhi. This research used quasy experimental methods with post test only control group design. Treatment consisted of 8 concentrations with 5 replications was 2,5 µg/disc, 5 µg/disc, 10 µg/disc, 20 µg/disc, 30 µg/disc, 40 µg/disc, 60 µg/disc, and 80 µg/disc. As much as 10 µl from each concentration was dropped into disc and placed in Mueller Hinton Agar. Then incubated for 18 hours to 37oC. Observation of bacterial inhibition zone by using a caliper. Result of this research that the leaf extract at a concentration 10 µg/disc, 20 µg/disc, 30 µg/disc, 40 µg/disc, 60 µg/disc, and 80 µg/disc can inhibit the growth of Salmonella typhi. Minimum Inhibitory Concentration of ethanolic extract from tempuyung leaf was 10 µg/disc qualitatively and 4,43 µg/disc quantitatively. Key words: Sonchus arvensis L., Salmonella typhi, antibacterial